ANALISIS STANDAR KINERJA DAN EVALUASI KINERJA PERANGKAT KELURAHAN : STUDI PADA KELURAHAN DEKET - Novi Dwi Fitriatunnisa; Diana Anggraeni; Adi Lukman Hakim (STKIP Subang, 2026)
This study aims to assess the performance and evaluation of village officials in Deket Village. The subjects included all village officials, with a population of approximately 30 individuals. The method used was qualitative, with data collection techniques including in-depth interviews, participant observation, and document analysis. Data were analyzed descriptively using a thematic approach to identify various factors influencing the achievement of performance standards and the effectiveness of performance evaluation. The research findings indicate that village officials have implemented the established performance standards, but there are several obstacles in implementing performance evaluation, such as limited human resources and administrative issues. This study recommends increasing the effectiveness of performance evaluation by strengthening the capacity of village officials, improving the documentation system, and using clearer and more measurable performance indicators. The results of this study are expected to serve as a guideline for other villages in improving their performance standards and village official evaluation processes.